Screening and characterization of sex-specific DNA fragments in the freshwater fish matrinch, Brycon amazonicus (Teleostei: Characiformes: Characidae) - da Silva, Eder Marques [UNESP]; Wong, Marina Sek Lien [UNESP]; Martins, Cesar [UNESP]; Wasko, Adriane Pinto [UNESP] (Springer, 2012)
The matrinch Brycon amazonicus, a commercially important freshwater fish resource, has no heteromorphic sex chromosomes so far described. In the present study, we performed a screening of sex-associated DNA markers in this species, through the use of a random amplified polymorphic DNA (RAPD) assay and a genomic DNA restriction digestion analysis. DNA digestions evidenced no differences between sexes. Sixty-six random primers were used in pooled and individual DNA samples of males and females, and the analysis of the RAPD fingerprints revealed one female sex-associated band. Cloning and sequencing of this band led to the identification of two distinct DNA segments. While one of the isolated fragments showed a significant identity with a described protein gene (phosphatidylinositol glycan anchor biosynthesis, class W), the other fragment, composed of 535 bp, corresponds to a novel DNA marker. Further experiments were performed with this second DNA fragment in order to verify its sex-specificity. Data on dot blot hybridization, using total DNA of both sexes, confirmed its female-specificity in B. amazonicus. A primer set was designed based on its sequence data and used in PCR with DNA samples of this species, leading to diagnose the animals' sexes with a 100 % overall accuracy through a sequence characterized amplified region approach. No amplification results were found for two other species of the genus-B. orbignyanus and B. lundii. The obtained data can lead to the hypothesis that B. amazonicus may present heteromorphic sex chromosomes that should be in an early phase of differentiation.
Keywords: Brycon; RAPD-PCR; Enzyme digestion; Sex-specific DNA marker; Sexing